SOCIAL PROCESSES IN THE FORMATION OF DRE PARKER’S CHARACTER IN "KARATE KID" FILM (2010) - Andriana, Wahyu Sartika; Natsir, M.; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2018)
ABSTRACT There are two objectives of research in this study, such as, to show the character formation that occurred in the character of Dre in Karate Kid film 2010, and to analyze how Dre experienced character changes shaped by social processes in Karate Kid film 2010. This analysis includes to descriptive qualitative method. This researcher used the Karate Kid film 2010 as the source of data. The data derived from the utterances of major characters containing the elements of social processes. From the finding of this analysis, the elements of social processes there are two classifications, first is associative social process, in associative social process such as; cooperation (team work), accommodation (agreement), assimilation (cultural fusion). The second classification of social process is dissociative social process, in dissociative social process such as; competition (compete in a good way), conflict (compete in a bad way). Keywords: individual, character formation, social process, hierarchy needs  ABSTRAK  Ada dua tujuan penelitian dalam penelitian ini, seperti, untuk menunjukkan pembentukkan karakter yang terjadi pada karakter Dre dalam film Karate Kid 2010, dan untuk menganalisis bagaimana Dre mengalami perubahan karakter yang dibentuk oleh proses sosial di film Karate Kid 2010. Analisis ini termasuk dalam metode deskriptif kualitatif. Peneliti ini menggunakan film Karate Kid 2010 sebagai sumber data. Data berasal dari ujaran karakter utama yang mengandung unsur-unsur proses sosial. Dari analisis ini, unsur-unsur proses sosial ada dua klasifikasi, pertama adalah proses sosial asosiatif, dalam proses sosial asosiatif seperti; kerjasama (kerja tim), akomodasi (kesepakatan), asimilasi. Klasifikasi kedua proses sosial adalah proses sosial disosiatif, dalam proses sosial disosiatif seperti; kompetisi (bersaing dengan cara yang baik), konflik (bersaing dengan cara yang buruk). Kata kunci: individu, pembentukkan karakter, proses sosial, kebutuhan hierarki